2005
DOI: 10.4321/s0365-66912005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Rabdomiosarcoma orbitario: dificultades en el Protocolo de Tratamiento Europeo

Abstract: Management of orbital rhabdomyosarcoma following the European Protocol leads to poor results compared with the American protocol. Early radiotherapy and complete tumoral excision could play a role in management of this tumour

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…24 – 26 Cassady et al 27 reported that high-dose RT decreases disease recurrence after orbital exenteration. In addition, Olivier Pascual et al 7 found that early RT and complete tumorectomy may be important for the treatment of orbital rhabdomyosarcoma. However, patients who undergo primary surgery suffer blindness, disfigurement, and pain, which significantly affects their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…24 – 26 Cassady et al 27 reported that high-dose RT decreases disease recurrence after orbital exenteration. In addition, Olivier Pascual et al 7 found that early RT and complete tumorectomy may be important for the treatment of orbital rhabdomyosarcoma. However, patients who undergo primary surgery suffer blindness, disfigurement, and pain, which significantly affects their quality of life.…”
Section: Discussionmentioning
confidence: 99%